HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP TERHADAP TINDAKAN PENCEGAHAN CORONAVIRUS DISEASE 2019 (COVID-19) PADA MAHASISWA KESEHATAN MASYARAKAT UPN VETERAN JAKARTA - Amari Akbar, (2020)
Coronavirus is a group of viruses that can cause disease in animals or humans. Coronavirus can attack the human body's immune system accompanied by general signs and symptoms such as symptoms of acute respiratory disorders such as shortness of breath, fever, and cough. However, in some cases, many young people are infected with Coronavirus and show no symptoms or minimal symptoms. The purpose of this study was to determine the relationship between the level of knowledge and attitudes of active students of the Undergraduate Public Health UPN Veteran Jakarta against Coronavirus Disease 2019 (COVID-19). This research method is a quantitative analytic with design cross-sectional. The sampling technique used accidental sampling with a sample of 232 active students of UPNVJ Public Health S1. Data collection using an electronic questionnaire. Data analysis in this research was univariate analysis and bivariate analysis with Chi-Square. The results of this study indicate that there is a relationship between knowledge (p-value = 0,000) and attitude (p-value = 0,000) towards COVID-19 preventive measures. Therefore, it is recommended that students care more about the health of themselves and others, and always improve their knowledge and attitudes so that they can apply COVID-19 preventive measures well for the maintenance of a healthy body and can break the chain of transmission of the virus.